(3CLhHI GHf eJGdis - (3eMePGf aGd Hf ebGdj GdJfOZj GdeQGHWj,J (B1282 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3SFd Yf bhdge GdLeGYI Jbhe ebGe GdMGce aCLGH HCf Pdc de jJMQQ dg eMd hSFd Yf GdYHO GdeMHS GdeKd Hg GdeMHS aCLGH HCfg jYJb hYdjg bjeg fedg s
(3BNQgG (B:s
(3abO PcQ YjGV ai GdTaGA Cfg dGjYPQ CMO ai GdcaQ HGdLgGdI hdG HOYhi Rdd GddSGf EdG ef CcQg hbdHg eWeFf HGdEjeGf s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeYgO GdehQjJGfi ddHMK GdYdei (B((3abg eGdc (B51) s
Keywords: (3Gdabg GdeGdcjs